Effect of Moringa Oleifera fortified porridge consumption on protein and vitamin A status of children with cerebral palsy in Nairobi, Kenya: A randomized controlled trial - Janet Kajuju Malla; Sophie Ochola; Irene Ogada; Ann Munyaka (Public Library of Science (PLoS), 2022)
Background Malnutrition due to inadequate dietary intake is commonly reported in children with Cerebral palsy (CP). Poor dietary intakes are majorly caused by feeding dysfunctions secondary to oro-motor impairment characteristic of the condition. Strategies that improve nutrient densities in foods can help enhance nutrient intakes by these children. Objective This study investigated the effect of consumption of fermented finger millet porridge fortified with Moringa oleifera leaf powder (MoLP) on the protein and vitamin A status of children with CP. Design A randomized controlled trial was conducted among 113 children aged 5-11 years with CP. The study had two arms (intervention [N = 57] and control [N = 56]). The intervention group received a daily serving of fortified finger millet porridge for 3 months while the control group received non-fortified finger millet porridge servings. All children received the same amounts of porridge servings. The levels of serum albumin and retinol between the groups were compared at both baseline and end line. The BMI-for-age Z-scores (BMIAZ) and morbidity prevalence of the children were also assessed. Results At baseline, the two study groups were similar in all demographic and socio-economic characteristics, nutrient intakes, serum levels of albumin and retinol, weight status and morbidity. At end line, the children from the intervention group had significantly higher intakes of vitamin A at 717.12±432.7 μg/d (p = 0.038) and protein at 44.367±17.2 g/d (p = 0.031) respectively. The serum nutrients levels increased significantly from baseline by 0.456±0.12 g/dL (p<0.001) for albumin and by 0.243±0.10 μmol/L (p<0.001) for retinol among children in the intervention group. Among the children in the control group, the changes in the levels of both serum albumin 0.012±0.07 g/dL (p = 0.868) and serum retinol [0.0021±0.02 μmol/L (p = 0.890)] were not significant. At endline, the BMI-for-age Z-scores results showed that 10.52% and 34.0% of children from intervention and control group respectively were undernourished [χ2 = 30.985; p = 0.037]. Among the children in the intervention, group there was a significant change in the weight status between baseline and endline (p = 0.036). The weight status among children in the control group was not significantly different between baseline and endline (p = 0.109). Significant difference in morbidity prevalence between the two groups was also observed at endline (p = 0.003) with the prevalence being 24.6% and 51.8% among children in the intervention and control group respectively. Conclusion Consumption of M. oleifera fortified porridge significantly improved the children's serum albumin and retinol levels, as well as BMIAZ. Registration number and name of trial registry The trial is registered at Pan African Clinical Trials Registry, number PACTR202107669905145 URL link: https://pactr.samrc.ac.za/.